Illness perceptions and health literacy are strongly associated with health-related quality of life, anxiety, and depression in patients with coronary heart disease: results from the EUROASPIRE V cross-sectional survey - Jennings, C S; Astin, F; Prescott, E; Hansen, T; Gale Chris, P; De Bacquer, D (European journal of cardiovascular nursing : journal of the Working Group on Cardiovascular Nursing of the European Society of Cardiology, 2023)
To (1) Describe the sociodemographic and risk factor profiles of a sample of patients with coronary disease, (2) Explore associations between illness perceptions and health literacy with sociodemographic characteristics and risk factors, health-related quality of life (HRQoL), anxiety, and depression.AIMSTo (1) Describe the sociodemographic and risk factor profiles of a sample of patients with coronary disease, (2) Explore associations between illness perceptions and health literacy with sociodemographic characteristics and risk factors, health-related quality of life (HRQoL), anxiety, and depression.Conducted as part of the ESC Prevention of CVD Project and EUROASPIRE V survey, patients were consecutively and retrospectively identified 6 months to 2 years after an acute event or elective procedure from 12 countries and interviewed. Three thousand four hundred and eight participants (76% male, mean age 64 years) were recruited, 16% were smokers, 38% obese, 60% physically inactive, and 41% hypertensive. Forty percent had attended cardiac rehabilitation. More threatening illness perceptions were associated with female gender (P < 0.0001), lower income (P < 0.0001), lower education (P = 0.02), obesity (P < 0.0001), sedentary behaviour (P < 0.0001), and diabetes (P < 0.0001). Poorer health literacy was associated with obesity (P = 0.02) and sedentary behaviour (P = 0.0001). Threatening illness perceptions were strongly associated with anxiety, depression, and poorer ratings of HRQoL after multivariable adjustment (all P < 0.001). Poor health literacy was associated with anxiety and depression (P < 0.0001) and poorer ratings of HRQoL (HeartQol scores P = 0.03). Results were consistent across regions of Europe, age, gender, and socio-economic strata.METHODS AND RESULTSConducted as part of the ESC Prevention of CVD Project and EUROASPIRE V survey, patients were consecutively and retrospectively identified 6 months to 2 years after an acute event or elective procedure from 12 countries and interviewed. Three thousand four hundred and eight participants (76% male, mean age 64 years) were recruited, 16% were smokers, 38% obese, 60% physically inactive, and 41% hypertensive. Forty percent had attended cardiac rehabilitation. More threatening illness perceptions were associated with female gender (P < 0.0001), lower income (P < 0.0001), lower education (P = 0.02), obesity (P < 0.0001), sedentary behaviour (P < 0.0001), and diabetes (P < 0.0001). Poorer health literacy was associated with obesity (P = 0.02) and sedentary behaviour (P = 0.0001). Threatening illness perceptions were strongly associated with anxiety, depression, and poorer ratings of HRQoL after multivariable adjustment (all P < 0.001). Poor health literacy was associated with anxiety and depression (P < 0.0001) and poorer ratings of HRQoL (HeartQol scores P = 0.03). Results were consistent across regions of Europe, age, gender, and socio-economic strata.Interventions like cardiac rehabilitation should be targeted at vulnerable groups given the strong associations between more threatening illness perceptions, lower health literacy, lower HRQoL, and higher levels of anxiety and depression. The delivery and content of these interventions should be accessible for those with low health literacy.CONCLUSIONSInterventions like cardiac rehabilitation should be targeted at vulnerable groups given the strong associations between more threatening illness perceptions, lower health literacy, lower HRQoL, and higher levels of anxiety and depression. The delivery and content of these interventions should be accessible for those with low health literacy.